CALR mutation screening in pediatric primary myelofibrosis. Issue 12 (30th August 2014) - An, Wenbin; Wan, Yang; Guo, Ye; Chen, Xiaojuan; Ren, Yuanyuan; Zhang, Jingliao; Chang, Lixian; Wei, Wei; Zhang, Peihong; Zhu, Xiaofan
<x xml:space="preserve">Abstract</x> Background Primary myelofibrosis (PMF) is quite rare in children. Mutations of JAK2V617F or MPLW515K/L were absent in pediatric patients with PMF according to previous studies. Recently, mutations in calreticulin (CALR) were described in adult patients with JAK2/MPL‐unmutated PMF. Our study aimed to analyze the clinical and genetic features of Chinese pediatric patients with PMF. Procedures We retrospectively investigated 14 pediatric patients diagnosed as PMF according to WHO 2008 criteria. Direct sequencing was performed for the existence of genetic alterations in JAK2, MPL, TET2, CBL, ASXL1, IDH1, IDH2, SRSF2, EZH2, DNMT3A and CALR. Results In our cohort, all patients had anemia, three patients (21%) had splenomegaly, six patients (43%) had micromegakaryocytes at time of diagnosis. No patient had spontaneous remission and six patients (43%) transformed to acute myelocytic leukemia. In nine patients with evaluable cytogenetic information, three subjects (33%) had abnormal karyotypes. The median survival from time of diagnosis was 28 months. Seven patients (50%) had type 2 mutations of CALR. No patient had mutations in the other candidate genes. There was no statistical differences in age, gender, hemoglobin, WBC, neutrophil and platelet counts, percentage of circulating blast, overall survival and leukemia transformation between patients with and without CALR mutation. Conclusion Our study documented that Chinese pediatric patients with PMF in our cohort had its own clinical characteristics and poor outcome. CALR mutations were detected in 50% of our pediatric patients with PMF. Based on our study, CALR mutations screening could be used as molecular marker for diagnosis of pediatric patients with PMF. Pediatr Blood Cancer 2014;61:2256–2262. © 2014 Wiley Periodicals, Inc.